The effects of popular television on the beliefs of Singaporean Christian youths. - Yong, Kuan Leong. (2008)
This project looks into the effects of televised violence and televised sexuality found on Singaporean Television (defined as TCS 5, TCS 8, Prime 12 and Premier 12) with regards to the fundamental religious beliefs of young Christians/Catholics in Singapore.